Role of epithelial sodium channel-related inflammation in human diseases - Chen, Yabin; Yu, Xiao; Yan, Zhiping; Zhang, Shuijun; Zhang, Jiacheng; Guo, Wenzhi (Frontiers in Immunology, 2023)
The epithelial sodium channel (ENaC) is heterotrimer, widely distributes in the kidney, blood vessel, lung, colon and many other organs. The basic role of ENaC is to mediate the entry of Na + into cells, ENaC also has an important regulatory function in blood pressure, airway surface liquid (ASL) and endothelial cell function. Aldosterone, serum/glucocorticoid kinase 1 (SGK1), shear stress, posttranslational modifications can regulate the activity of ENaC, some ion channels also interact with ENaC. In recent years, it has been found that ENaC can lead to immune cells activation, endothelial cells dysfunction, aggravated inflammation involved in high salt-induced hypertension, cystic fibrosis, pseudohypoaldosteronism (PHA), tumor and other diseases, some inflammatory This is a provisional file, not the final typeset article cytokines have been reported to have a regulatory role on ENaC. ENaC hyperfunction mediates the increase of intracellular Na + , elevated exchange of Na + with Ca 2+ leads to intracellular calcium overload, which is an important mechanism for ENaC-related Inflammation. Meanwhile part of research on ENaC is controversial or unclear, we review the progress of studies on role of ENaCrelated inflammation in human diseases and their mechanisms.